SAFEGUARDING FINANCIAL STABILITY, PROMOTING TRADE: THE ROLE OF THE INDONESIA DEPOSIT INSURANCE CORPORATION IN INDONESIA’S EXPORT–IMPORT PERFORMANCE - Syilvana Dwi Novianti; Andri Soemitra; Anggi Pratiwi Sitorus (Journal of Development Economics and Digitalization, Tourism Economics, 2026)
This study examines the role of the Indonesia Deposit Insurance Corporation in safeguarding financial stability and its implications for Indonesia’s export–import performance. While deposit insurance schemes are primarily designed to maintain confidence in the banking system, their broader macroeconomic effects particularly on international trade remain underexplored. This research addresses this gap by analyzing the transmission mechanism from deposit insurance policy to trade performance through financial stability channels. Using a Structural Vector Autoregression (SVAR) framework, the study employs five key variables: the guaranteed interest rate set by the deposit insurance authority as a proxy for deposit insurance policy, the non-performing loan ratio as an indicator of banking sector stability, the policy interest rate, the exchange rate, and export performance. Quarterly time-series data for Indonesia are utilized to capture dynamic interactions and structural shocks among policy, financial, and real-sector variables.The impulse response analysis reveals that shocks to deposit insurance policy contribute to improvements in banking stability, reflected in lower non-performing loan ratios, which subsequently support export performance over the medium term. These findings suggest that deposit insurance institutions play a broader macroeconomic role beyond financial safety nets, indirectly fostering trade performance by enhancing financial system resilience. The study provides important policy insights by highlighting the strategic contribution of deposit insurance to financial stability and international trade, reinforcing the need for coordinated financial and trade policies in emerging economies.